Primer Siliyer Diskinezili ve Sağlıklı Çocuklarda Aerobik Kapasitenin Karşılaştırılması - Senem Şimşek; Deniz İnce; Aslıhan Çakmak; Ebru Kütükcü; Melda Sağlam; Naciye Yağlı; Nagehan Emiralioğlu; Uğur Özçelik; Hazal Sonbahar; Cemile Özdemir; Hülya Arıkan; Nural Kiper (Hacettepe University, 2014)
Purpose: Information regarding the effects of primary ciliary dyskinesia (PCD), a rare usually autosomal recessive disease, on exercise capacity is limited. In this study, we aimed to compare aerobic capacity of children with PCD those with age-and sex matched healthy counterparts. Material and Methods: Fifteen patients with PCD (13.1±3.1 years) were participated, and 15 age- and sex- matched healthy children (13.3±3.2 years) were enrolled as controls. Patients underwent pulmonary function testing, a modified shuttle walk test was performed. Heart rate, blood pressure, oxygen saturation (Sa02), and fatigue were recorded before and after the exercise test. Results: Physical characteristics of the two groups were similar (p>0.05). The PCD subjects' forced vital capacity (FVC), forced expiratory volume in one second (FEV1), forced expiratory flow between 25% and 75% (FEF25-75%), forced expiratory flow at 25% (FEF25%), forced expiratory flow at 50% (FEF50%), forced expiratory flow at 75% (FEF75%), peak expiratory flow (PEF), shuttle walk test distance, and peak exercise heart rate, Sa02 values during exercise were significantly lower than those of healthy subjects (p<0.05). Discussion: Pulmonary function and maximal aerobic capacity in patients with PCD are negatively affected at an early stage. The effects of exercise training, exercise capacity and airway clearance in PCD patients should be investigated.